Influence of melt convection on the dynamics and capture inclusions for growing oxide crystals by HDC - Naydenov, S.V.; Nizhankovskiy, S.V.; Tan′ko, A.V.; Grin′, L.A.; Baranov, V.V. (Functional Materials, 2015)
The main properties of motion of gas-vapor bubbles and impurity inclusions in hydrodynamic flows are considered. It is founded the criteria for the formation of the defective areas for crystal growth of oxide crystals by horizontal directional solidification which is depended on the hydrodynamic and geometrical parameters of the melt convection.